miR-17-5p is highly expressed in patients with lung cancer and promoted lung cancer by targeting SIK1 - Xiaoyan Chen; Shanna Su; Jingyi Liu; Dong Zhang; Guangliang Qiang (Discover Oncology)
Abstract Background This study aimed to investigate the expression and role of miR-17-5p in lung cancer. Methods The levels of miR-17-5p in four non-small cell lung cancer cell lines and human normal lung epithelial cells (BEAS-2B) were detected by fluorescent quantitative PCR. Next, the cell lines with relatively high expression of miR-17-5p were treated with miR-17-5p mimics, miR-17-5p inhibitor or control miRNA. CCK8, flow cytometry analysis, and Transwell assay were used to analyze cell proliferation, apoptosis, invasion, and migration. The target genes of miR-17-5p were predicted based on Starbase and Targetscan databases, and the interaction between miR-17-5p and SIK1 was verified by luciferase assay. Results miR-17-5p was highly expressed in lung cancer tissues of patients with lung cancer. Overexpression of miR-17-5p significantly promoted lung adenocarcinoma cell proliferation, invasion, and migration, and inhibited apoptosis. There was a direct binding site between miR-17-5p and SIK1 3'UTR, and overexpression of miR-17-5p inhibited the expression of SIK1 at both mRNA and protein levels. Conclusion Our findings suggest that miR-17-5p may promote lung adenocarcinoma by targeting SIK1 and may be a potential biomarker for lung cancer.